Screening for onconeural antibodies in neuromyelitis optica spectrum disorders - Berger, Benjamin (BMC Neurol, 2017)
BACKGROUND: Some so-called “non-classical” paraneoplastic neurological syndromes (PNS), namely optic neuritis and myelitis, clinically overlap with neuromyelitis optica spectrum disorders (NMOSD), and conversely, in cancer-associated NMOSD, a paraneoplastic etiology has been suggested in rare cases. Therefore, we retrospectively investigated the prevalence of onconeural antibodies, which are highly predictive for a paraneoplastic etiology, and the prevalence of malignancies in NMOSD patients. METHODS: We retrospectively screened 23 consecutive patients from our clinic with NMOSD (13 were anti-aquaporin-4 [AQP4] antibody positive, 10 were AQP4 negative) for onconeural antibodies using an immunoblot. RESULTS: All patients were negative for a broad spectrum of antibodies targeting intracellular onconeural antigens (Hu, Yo, Ri, CV2/CRMP5, Ma1, Ma2, Zic4, SOX1, Tr, and amphiphysin). Notably, only two patients had a malignancy. However, neoplastic entities (astrocytic brain tumor and acute myeloid leukemia) were not typical for PNS. CONCLUSIONS: Our data suggest that there is no need to routinely screen anti-AQP4 antibody positive NMOSD patients with a typical presentation for onconeural antibodies. Furthermore, absence of these antibodies in NMOSD, which is typically non-paraneoplastic, confirms their high specificity for PNS.